If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(2-3v)-4v=6(v-6)
We move all terms to the left:
-6(2-3v)-4v-(6(v-6))=0
We add all the numbers together, and all the variables
-6(-3v+2)-4v-(6(v-6))=0
We add all the numbers together, and all the variables
-4v-6(-3v+2)-(6(v-6))=0
We multiply parentheses
-4v+18v-(6(v-6))-12=0
We calculate terms in parentheses: -(6(v-6)), so:We add all the numbers together, and all the variables
6(v-6)
We multiply parentheses
6v-36
Back to the equation:
-(6v-36)
14v-(6v-36)-12=0
We get rid of parentheses
14v-6v+36-12=0
We add all the numbers together, and all the variables
8v+24=0
We move all terms containing v to the left, all other terms to the right
8v=-24
v=-24/8
v=-3
| -6b-7=-5-7b | | 13+5x=-72 | | X^2-6x-14=3 | | -9x-9+7x=8 | | 13+5x=-75 | | 3a+10+44=540 | | 3-6r+8r=2r-1 | | 17-8x=33 | | (-3k-15=k-(4K+7) | | –7z+–13=8 | | -16+8x=x+5 | | -5=1/4m | | -4x-5-1=-6-4x | | {5x}{7}=5 | | 9(x-1)+3=6x+3(5+x) | | 52+13=17p | | 3(x-1)=-2x+3 | | r+35=27 | | -7-k=4k-4k | | -2y+9=-3(2y | | 23=d+9 | | -104=8(2x-1) | | 5n-(6n-1)=-5+5n | | 4b=37 | | -5-4v=7+2v | | -6-42k=-8+42k | | z/4+22=30 | | 2{n+1/3}=3/2n+1+1/2n-1/3 | | 44=-22p | | 9(x-4)-7x=-5(-3x+2) | | 7w+1=0 | | 3/16y=y/1+13 |